Anti-tumor effect of inhibition of IL-6 signaling in mucoepidermoid carcinoma - Mochizuki, Daiki (Oncotarget, 2015)
Mucoepidermoid carcinoma (MEC) is the most frequent malignant salivary gland cancer. Response to chemoradiotherapy is modest, and therefore radical surgery remains the standard-of-care. Emerging evidence suggests that Interleukin (IL)-6 signaling correlates with the survival of cancer stem cells and resistance to therapy. Here, we investigated whether inhibition of IL-6 receptor (IL-6R) signaling with tocilizumab (humanized anti-human IL-6R antibody) sensitizes MEC to chemotherapy using human mucoepidermoid carcinoma cell lines (UM-HMC) and correspondent xenograft models. In vitro, we observed that tocilizumab inhibited STAT3 phosphorylation but had no measurable effect in MEC cell viability (UM-HMC-1,-3A,-3B). In contrast, the anti-tumor effect of single agent tocilizumab on MEC xenografts was comparable to paclitaxel or cisplatin. Combination of tocilizumab with cisplatin or paclitaxel enhanced the inhibitory effect of chemotherapy on xenograft growth (P < 0.05), time to failure (P < 0.01), decreased vascular endothelial growth factor (VEGF) expression and tumor microvessel density (P < 0.05) without added systemic toxicities. Notably, tocilizumab decreased the fraction of MEC cancer stem cells (ALDH(high)CD44(high)) in vitro, and prevented paclitaxel-induced increase in the fraction of cancer stem cells in vivo (P < 0.05). Collectively, these findings demonstrate that tocilizumab enhances the anti-tumor effect of conventional chemotherapy in preclinical models of mucoepidermoid carcinoma, and suggest that patients might benefit from combination therapy with an inhibitor of IL-6R signaling and chemotherapeutic agent such as paclitaxel.